Development and Validation of an LC-MS/MS-ESI Method for Comparative Pharmacokinetic Study of Ciprofloxacin in Healthy Male Subjects - Choudhury, Hira; Gorain, Bapi; Paul, Anwesha; Sarkar, Pradipta; Dan, Shubhasis; Chakraborty, Pragnya; Pal, Tapan K (Drug research, 2017)
A sensitive, specific and reproducible liquid chromatography coupled to tandem mass spectrometric method was developed and validated for the estimation of ciprofloxacin, an extensively used second-generation quinolone antibiotics, in human plasma. A liquid-liquid extraction of ciprofloxacin and the internal standard, ofloxacin, has been approached from the biological matrix using chloroform. Chromatographic separation was achieved in positive ion modes, isocratically on a 3.5 μm C18 analytical column (75 mm×4.6 mm, i.d.) with 0.2% formic acid solution in water: methanol (10:90, v/v) as mobile phase, at a flow rate of 0.5 mL.min . The MS/MS ion transitions were monitored as 332.0→231.3 for ciprofloxacin and 362.2→261.0 for IS. The method showed good linearity in the range of 0.01-5.00 μg.mL ( >0.99) with a good precision (3.37-12.60%) and accuracy (87.25-114%). At the same time, ciprofloxacin was found to be stable during stability studies viz. bench-top, auto-sampler, freeze-thaw cycle and long-term. The developed and validated method was successfully applied to measure plasma ciprofloxacin concentrations in a single dose bioequivalence study.